Pean Billroth I Gastrectomy for Gastric Ulcer - Aliano, Artigas; Schneeberger, Federico; Montandon, Pablo (Cirugía del Uruguay, 1979)
Preiiminary report on prospective study of the advantages of "bit by bit" gastric resection in cases of gastric ulcers, restablishing transit by Pean - Billroth I technique. The paper contains an analysis of indications and of immediate results in 16 patients